Protominérios e minérios de manganês de Juá-CE - Gomes, Elenilza Nascimento (2013)
The district Juá located between the municipalities of Choró and Quixadá in the state of Ceará, manganese occurrence records from the supergene enrichment of lenses and bands protominérios metamorphic silicate and silica-carbonate intercalated biotite gneisses Unit Cottons. The main occurrences are oriented EW to NW-SE to inflections, the ore bodies are boudinados and folded along with the host rocks of gneiss unit Cottons as a result of ductile deformation Brasiliana. The ruptile tectonics is also recorded in the area, as evidenced by the orientation of the main watercourses and systems of fractures observed in lithologies mapped according to orientations preferred NW-SE and NE-SW. The petrographic, mineral chemistry and X-ray diffraction enabled the differentiation of two main types of protominérios manganese: a predominantly manganesífera garnet (spessartine) and another where the ore is the mineral rhodonite (pyroxene manganesíferos). Both of protominérios essentially correspond to silicate containing varying amounts of oxides of silicon and aluminum. The supergene enrichment of protominérios generated massive ore containing pyrolusite, manganite, cryptomelane and todorokite in varying proportions. Apparently the pyrolusite and cryptomelane represent the dominant phases of the richest ores. The protominérios derived metamorphic reaction past tenses sediment containing (silicates, carbonates and oxides of manganese). Apparently the pyrolusite is the dominant phase of the richest ores.